2021
DOI: 10.14254/jems.2021.6-2.7
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perceptions to support Jurassic Park project as a future wildlife tourism

Abstract: Tourism in protected areas contributes to the financial sustainability of its sites. It has a positive impact on a stakeholder within and beyond the destinations through effective and efficient benefitsharing. This study examine the environmental attitudes, community attachment, economic gain, and community involvement that will impact to the stakeholder perceptions to revitalization project in Komodo National Park, Indonesia. In the context of protected areas of World Heritage Sites by UNESCO, this project re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…A study conducted in 2015 has shown that residential and tourism infrastructures have skyrocketed in the areas of Labuan Bajo (Lasso & Dahles, 2021). By 2020, the project was extended to protected areas of World Heritage Sites by UNESCO to develop tourism infrastructure that the media said was a Jurassic Park Theme instead of nature-based tourism (Choirisa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in 2015 has shown that residential and tourism infrastructures have skyrocketed in the areas of Labuan Bajo (Lasso & Dahles, 2021). By 2020, the project was extended to protected areas of World Heritage Sites by UNESCO to develop tourism infrastructure that the media said was a Jurassic Park Theme instead of nature-based tourism (Choirisa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in 2015 has shown that residential and tourism infrastructures have skyrocketed in the areas of Labuan Bajo (Lasso & Dahles, 2021). By 2020, the project was extended to protected areas of World Heritage Sites by UNESCO to develop tourism infrastructure that the media said was a Jurassic Park Theme instead of nature-based tourism (Choirisa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%